Real Lives and Lost Lives: making Sense of ‘Locked in’ Responses to Intimate Partner Homicide - Walklate, Sandra (Asian journal of criminology, 2019)
The problem of intimate partner homicide is featuring increasingly on national and international policy agendas. Over the last 40 years, responses to this issue have been characterised by preventive strategies (including ‘positive’ policing; the proliferation of risk assessment tools, and multi-agency working) and post-event analyses (including police inquiries and domestic homicide reviews). In different ways, each of these responses has become ‘locked in’ to policies. Drawing on an analysis of police inquiries into domestic homicides in England and Wales over a 10-year period, this paper will explore the nature of these ‘locked in’ responses and will suggest that complexity theory offers a useful lens through which to make sense of them and the ongoing consistent patterning of intimate partner homicide more generally. The paper will suggest this lens in embracing what is known and unknown affords a different way of thinking about and responding to this problem.